Damped jump-telegraph processes (2013)
We study a one-dimensional Markov modulated random walk with jumps. It is assumed that the amplitudes of the jumps as well as the chosen velocity regime are random, and depend on the time spent by the process at the previous state of the underlying Markov process.Equations for the distribution and equations for its moments are derived. We characterise the martingale distributions in terms of observable proportions between the jump and velocity regimes. © 2013 Elsevier B.V.